Analisis Pendidikan didalam Tradisi Kenduri sebagai Bentuk Kearifan Lokal dalam Budaya Jawa di Dusun Jati Desa Ngrogung Kecamatan Ngebel Kabupaten Ponorogo - Anam, Rischi Shoirul; Yuli Ani Setyo Dewi (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The kenduri tradition is one form of local wisdom of Javanese society that still exists today and is widely practiced across various regions of Java Island, carried out as an expression of gratitude to God Almighty. This local wisdom continues to be preserved, including in Dusun Jati, Ngrogung Village, Ngebel Sub-district, Ponorogo Regency. This study aims to understand the meaning of kenduri as a religious tradition as well as a socio-cultural value inherited from generation to generation by the ancestors. The method employed in this research is qualitative with an ethnographic approach, through interviews with local community leaders, direct observation, and documentation collection. The findings of this research indicate that kenduri not only functions as a medium of collective prayer and an expression of gratitude to God Almighty, but also as a way to strengthen solidarity among the community, reinforce the value of mutual cooperation, and preserve Javanese cultural traditions. The implementation of kenduri in Dusun Jati involves community participation from the preparation, prayer, to the distribution of berkat (food offerings). The local wisdom values contained in this tradition include togetherness, tolerance, solidarity, and cultural preservation. The conclusion of this research is that the kenduri tradition plays a crucial role in maintaining harmony within Javanese society amid the realities of modernization, making it essential to preserve and introduce to the younger generation so that such customs may continue and not disappear due to the advancement of the times.